2020
DOI: 10.9734/ajrb/2020/v6i130107
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Antioxidant Activity of Stalk and Fruit of Solanum aethiopicum L. (Solanaceae)

Abstract: Background: The use of plants for healing dates back to very remote times. Nowadays with the accession of new diseases plants are increasingly used for the formulation of new drugs able to overcome the many diseases (cancer, atherosclerosis) often caused by the disorder of the system prooxidant/antioxidant. Aim/Objective: On the strength of this observation, the research of an antioxidant plant is essential, hence the aim of this study, which is to determine the antioxidant activity of the stalk and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…Reports have shown that saponins present in traditional medicine preparations cause hydrolysis of glycosides from terpenoids which avert the toxicity associated with the intact molecule [61,62]. Ascorbic acid and flavonoids have been found to be present in the fruits and stalk of the plant, which contain high antioxidant potential [63][64][65]. Traditionally, many tropical African countries use the fruits of bitter cultivars as medicine to cure certain ailments [66].…”
Section: Phytochemical and Pharmacological Activitiesmentioning
confidence: 99%
“…Reports have shown that saponins present in traditional medicine preparations cause hydrolysis of glycosides from terpenoids which avert the toxicity associated with the intact molecule [61,62]. Ascorbic acid and flavonoids have been found to be present in the fruits and stalk of the plant, which contain high antioxidant potential [63][64][65]. Traditionally, many tropical African countries use the fruits of bitter cultivars as medicine to cure certain ailments [66].…”
Section: Phytochemical and Pharmacological Activitiesmentioning
confidence: 99%